2012
DOI: 10.4103/0973-1075.97475
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of "Quality of life": A systematic review and quantitative analysis of research publications in palliative care journals

Abstract: Context:Palliative care clinical practice depends upon an evidence-based decision-making process which in turn is based upon current research evidence. One of the most important goals in clinical palliative care is to improve patients’ quality of life (QoL).Aim:This study aimed to perform a quantitative analysis of research publications in palliative care journals for reporting characteristics of articles on QoL.Settings and Design:This was a systematic review of palliative care journals.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…This study is essentially the first of its kind of a review of palliative care journals utilizing a systematic approach to quantitatively identify reporting characteristics of articles on cancer-related fatigue (CRF (20). The reason why this study found a much smaller reporting rate could only be due to the relatively lesser emphasis given towards CRF in the palliative care journals.…”
Section: Discussionmentioning
confidence: 98%
“…This study is essentially the first of its kind of a review of palliative care journals utilizing a systematic approach to quantitatively identify reporting characteristics of articles on cancer-related fatigue (CRF (20). The reason why this study found a much smaller reporting rate could only be due to the relatively lesser emphasis given towards CRF in the palliative care journals.…”
Section: Discussionmentioning
confidence: 98%
“…Though endowed with simplicity and ease of use, the said questionnaire lacks the detailed structure as would more standardized questionnaires, such as the EORTC-H and N35 and FACT-G, for examples. [ 35 ],[ 36 ],[ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care journals have an increased responsibility to publish more systematic reviews and metaanalyses and based on the findings of Bhandari et al, 101 systematic reviews were more cited than narrative reviews 122 and the journals publishing more systematic reviews had higher impact factor, and was widely cited in specialty and non-specialty journals alike. Future studies on association of impact factor 123 with reporting characteristics in palliative care journals [18][19][20] on the quantity and quality of systematic reviews are needed. Indian Journal of Palliative Care being the only journal representing palliative care research in developing countries and Asia, it has a huge responsibility to publish more highlevel evidence hierarchy-based research to improve the global profile 124 …”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies on analysis of palliative care journals were on reporting of moral problems (ethical issues), 12 euthanasia, 13 chaplains and community-based clergy, 14,15 and, religion and spirituality, cancer pain, 18 pediatric palliative care 19 and quality of life. 20 The objective of this present study was to perform a bibliometric analysis of systematic reviews and meta-analyses in palliative care journals. 2.…”
Section: Introductionmentioning
confidence: 99%